Solve.Use the elimination method when solving the translated system.
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

If the numbers are a and b, then a+b=63 and a-b=9. From the first equation a=63-b, so we can substitute this value in the other: 63-b-b=9, 63-2b=9, so 2b=63-9=54 and b=27. From this value of b we can find a: a=27+9=36.

Another way to eliminate a or b is to add the two equations: 2a=72, so a=36; and subtract the second from the first: 2b=54, so b=27.

by Top Rated User (1.1m points)

Given x + y = 63.....(1)
& x - y = 9 .......(2)

Add (This eliminates 'y' (+ y - y = 0) )
2x = 72
x = 36
Subsitute 'x = 36' back into either equ'n to find 'y'.

 

Hence
36 + y = 63
y = 63 - 36
y = 27

Hence two numbers are 27 and 36


Algebra 1 Online Help

by Level 8 User (30.1k points)

Related questions

Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
87,548 questions
99,681 answers
2,417 comments
465,555 users